Boldly going where firms have gone before? Understanding the evolution of supplier codes of conduct. Issue 3 (12th August 2019) - Brockhaus, Sebastian; Fawcett, Stanley E.; Hobbs, Sammuel; Schwarze, Adoley Simone
Abstract : Purpose: Supplier codes of conduct (CoC) are the primary mechanism companies use to drive corporate social responsibility (CSR) upstream in their supply chains. Companies have traditionally used CoC to tackle systemic social issues (e.g. forced labor, wages and working conditions). More recently, CoC have included environmental concerns (e.g. waste treatment, toxic chemicals and pollution). The purpose of this paper is to analyze how companies have evolved their CoC across four points in time between 1999 and 2017. By evaluating changes in the scope, depth and possible regime of sanctions included in CoC, the authors consider whether companies use CoC as either a leveling or a differentiating mechanism. Design/methodology/approach: The authors employ a competing-theories approach to examine how companies have employed CoC. Specifically, the authors examine the content of CoC between four data points: 1999, 2005, 2010 and 2017 to determine whether CoC are used to maintain comparative parity (institutional theory) or to achieve a distinctive market presence (awareness–motivation–capability (AMC) framework). The sample includes 36 transnational companies. To enable replication, the authors maintained consistent sampling and coding procedures across the four time periods. Findings: The authors find a significant harmonization and standardization of CoC over time. Alignment occurs at the lower end of acceptable norms – i.e. a lowest-common-denominator approach. Companies have not chosen to take a more aspirational approach that involves raising the bar on social and environmental performance. That is, companies have not attempted to use CoC to differentiate themselves as CSR standard bearers. Provision specificity dropped for the 2010 sample before rebounding in 2017. Originality/value: The authors juxtapose the findings with a theoretical framework based on the tenets of institutional theory and the AMC framework. The authors conclude that changes in CoC are largely driven by coercive, normative and mimetic isomorphism as opposed to attempts to leverage CoC to create a distinctive image that could be used for competitive advantage. This finding provides context for how the public, investors and managers should view these documents.